Endothelial nitric oxide synthase 27VNTR (4b/4a) gene polymorphism and the risk of diabetic microvascular complications in Chinese populations - Zhang, X.; Yang, Z.; Chen, X. (Cellular and Molecular Biology, 2017)
To access the association of endothelial nitric oxide synthase (eNOS) gene 27VNTR (4b/4a) polymorphism with diabetic microvascular complications (DMI) susceptibility in Chinese populations. Data were retrieved in a systematic manner on PubMed database, ISI Web of Knowledge, the Cochrane Library, Chinese National Knowledge Infrastructure, and Wanfang, as well as manual searching of the references of the identified articles. Odds ratio (OR) and 95% confidence interval were used to evaluate the strength of associations. Potential sources of heterogeneity and publication bias were explored. Twelve published articles with thirteen outcomes including 1484 DMI patients and 1225 diabetic controls were included in the meta-analysis. The results showed no evidence for significant association of 27VNTR (4b/4a) polymorphism with DMI risk in dominant model (OR=1.36, 95% CI=0.90–2.06, P=0.15), and similar results were obtained in the allelic, additive and the recessive models (Pï¹¥0.05). Our meta-analysis suggests that eNOS gene 27VNTR (4b/4a) polymorphism might not be a risk factor for DMI in Chinese populations.